Aluzje z Księgi Sofoniasza w Nowym Testamencie? - Kotecki, Dariusz (Collectanea Theologica, 2018)
In the New Testament there are no citations from the Book of Zephaniah. There are only allusions which are understood as references to another work of literature thanks to which a given text uses the content of other literature to a greater or lesser extent as a way of expressing its own content. The author of the article analyses the following allusions: to Zep 1:3 in Mt 13:41; to Zep 3:8 in Rev 16:1; to Zep 3:13 in Rev 14:5 and to Zep 3,15 in Jn 1:49, asking about their importance and weight. He comes to the conclusion that some of them are very probable (e.g. Zep 1:3 in Mt 13:41; Zep 3:13 in Rev 14:5 or Zep 3,15 in Jn 1:49) and others should be viewed as the echo of prophetic texts (e.g. Zep 3:8 in Rev 16:1). However, in all cases we can observe the reinterpretation of the Book of Zephaniah in a new Christological (Zep 1:3 in Mt 13:41; Zep 3,15 in Jn 1:49), ecclesiological (Zep 3:13 in Rev 14:5) or theological (Zep 3:8 in Rev 16:1) context.